Produktivitas Terminal dan Kinerja Operasional di Pelabuhan Tanjung Priok - Syayuti, Faisyal; Thamrin, Muhammad; Majid, Suharto Abdul; Sihombing, Sarinah; Liana, Esti (Institut Transportasi dan Logistik Trisakti, 2023)
The study aims to find out the effect of loading and unloading workers’ performance and port facilities on the terminal productivity and the port operational’s performance in Tanjung Priok Port. The problems of the study are the low productivity of loading and unloading performance in the port, the lack of main facilities and supporting equipments could decrease the loading and unloading performance and unorganized service performance in the port. The research method used path analysis with Structural Equation Modeling using Smart PLS. The 152 samples were taken from Tanjung Priok Port service users. It is concluded that directly and indirectly there is a significant positive effect on the performance of the loading and unloading workforce and port facilities on terminal productivity and the impact on port operational performance in Tanjung Priok Port.